PERAN KEBIJAKAN EKSPORT PEMERINTAH TERHADAP PROSES INTERNASIONALISASI UMKM - Lusia Hartanti; Lulu Setiawati (Universitas Bunda Mulia, 2017)
Small and Medium Enterprises is one of locomotion the economy in Indonesia. It amounted to 56,5 millions units, whereas 99.8% of them are in the micro sector business. This thing causes government have to think the way to help small entrepreneurs to ease their business. INSW is Indonesia's national system which allows making acceleration in import-export process. Research method which is used in this research is case study. Data collected through interviews with small entrepreneur. The results of the study found that small entrepreneurs have not understood and take advantage of the policy that has been determined by the government. They hope that . Para pelaku bisnis mengharapkan the Government to be more proactive about INSW's policy of socialization do who have been there, so they can exploit it.